2006
DOI: 10.1182/blood-2006-06-025882
|View full text |Cite
|
Sign up to set email alerts
|

IgA Fc receptor I signals apoptosis through the FcRγ ITAM and affects tumor growth

Abstract: IntroductionThe receptor specific for the IgA Fc region (Fc␣RI or CD89) is expressed on blood myeloid cells, including monocyte/macrophages, dendritic cells, Kupffer cells, neutrophils, and eosinophils. 1 It transmits IgA-mediated effector functions via an IgA-binding module (K a about 10 6 M Ϫ1 ) that can be expressed with or without physical association with the disulfide-linked signaling adaptor FcR␥. 2,3 The FcR␥-associated receptor has signaling functions that involve an immunoreceptor tyrosine-based acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 41 publications
(51 reference statements)
0
25
0
Order By: Relevance
“…Previous work showed that monovalent targeting by anti-FcaRI Fab resulted in monocyte apoptosis (47) and prevented or suppressed inflammation in transgenic animal models of renal inflammation (36) and allergic asthma (19). In line with these observations, our study points to an immunoregulatory role for FcaRI, although monovalent targeting of neutrophils by anti-FcaRI Fab had no effect on their viability, and death induction required natural IgA or divalent F(ab9) 2 or whole anti-FcaRI Ab in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work showed that monovalent targeting by anti-FcaRI Fab resulted in monocyte apoptosis (47) and prevented or suppressed inflammation in transgenic animal models of renal inflammation (36) and allergic asthma (19). In line with these observations, our study points to an immunoregulatory role for FcaRI, although monovalent targeting of neutrophils by anti-FcaRI Fab had no effect on their viability, and death induction required natural IgA or divalent F(ab9) 2 or whole anti-FcaRI Ab in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…IgA binding to FcaRI in the absence of sustained aggregation inhibits cellular responses initiated by a heterologous receptor and mediates apoptosis, while sustained clustering of FcaRI by IgA-IC leads to cell activation [11,12]. The multiple functions of FcaRI provide a molecular basis for the opposite roles of IgA as both an anti-and proinflammatory isotype [32].…”
Section: Discussionmentioning
confidence: 99%
“…Only the latter complex shows signal competence, as it bears an ITAM in the FcRc intracellular tail. It mediates either inflammatory or anti-inflammatory signaling, depending on multivalent or monovalent receptor targeting [11,12]. While monomeric IgA induces inhibition of heterologous receptors and apoptosis [11], multivalent aggregation of FcaRI by IC triggers several activating functions, including phagocytosis, superoxide production, and inflammatory cytokine secretion such as tumor necrosis factor-a (TNF-a) and interleukin-6 (IL-6) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Myeloid cell-expressed Fc␣RI and its associated ITAM-bearing FcR␥ subunit have recently emerged as new actors in immune homeostasis (19,20,40). They act as a dual-function module that can either activate cells or attenuate cell activation through heterologous ITAM-bearing receptors, depending on the interaction with its ligand.…”
Section: Discussionmentioning
confidence: 99%